On models of Kirchhoff Equations with damping terms: existence results and asymptotic behaviour of solutions - Yusuf, Owolabi (Department of Mathematics and Applied Mathematics, 2019)
The abstract will be viewed from the PDF to distortion Mathematical Formulas.